Forecasting Remittance Inflow in Nepal Using the Box-Jenkins ARIMA Model - Devkota, Bhim Prakash; Pokhrel, Sudip (Kathford Journal of Engineering and Management, 2023)
The remittance, defined as a portion of household income sent by individuals from their earnings in foreign economies, constitutes a substantial aspect of Nepal’s current financial landscape. This research endeavors to identify an appropriate ARIMA model to forecast the remittance inflow in Nepal from 1990/91 to 2021/22. The Box-Jenkins methodology serves as the framework for modeling and forecasting the annual remittance inflow, with EViews 12 software employed for comprehensive data analysis. Various ARIMA models were evaluated to capture nuances in annual remittance trends. The investigation identified the ARIMA (1,1,1) model as the most suitable for forecasting Nepal’s remittance inflow. This finding provides essential insights for policymakers, economists, and stakeholders, facilitating informed decisionmaking and future economic planning in the country.